Lithium‐Metal Anodes: Bending‐Tolerant Anodes for Lithium‐Metal Batteries (Adv. Mater. 1/2018). Issue 1 (2nd January 2018) - Wang, Aoxuan; Tang, Shan; Kong, Debin; Liu, Shan; Chiou, Kevin; Zhi, Linjie; Huang, Jiaxing; Xia, Yong‐Yao; Luo, Jiayan
Abstract : Lithium has many challenges, especially its tendency to form dendrites. Under bending conditions in cylindrical or flexible cells, lithium‐dendrite growth can be further aggravated due to local plastic deformation and pulverization of lithium filaments. In article number1703891, Jiayan Luo and co‐workers fabricate bending‐tolerant lithium‐metal anodes by integrating the lithium into bendable scaffolds, such as reduced graphene oxide films.